International Financial Statistics, June 2018. (International Financial Statistics; International Financial Statistics ;, 2018)
This paper discusses that Special Drawing Rights (SDRs) have been allocated by the IMF to members that are participants in the SDR Department (at the time of allocation) in proportion to their quotas in the IMF. Six allocations, totaling 21.4 billion SDR, were made by the IMF in 1970, 1971, 1972, 1979, 1980, and 1981. In addition, a general allocation of 161.2 billion SDR was made on August 28, 2009, and a special allocation of 21.5 billion SDR was made on September 9, 2009. The IMF cannot allocate SDRs to itself, but can receive them from members through various financial transactions and operations. Entities authorized to conduct transactions in SDRs are the IMF itself, participants in the SDR Department, and other prescribed holders. The SDR can be used for a wide range of transactions and operations, including for acquiring other members' currencies, settling financial obligations, making donations, and extending loans.